Experimental investigation on the influence of evaporative cooling of permeable pavements on outdoor thermal environment - Wang, Junsong; Meng, Qinglin; Tan, Kanghao; Zhang, Lei; Zhang, Yu (Building and environment, 2018)
Permeable pavements are effective in mitigating the urban heat island effect via evaporative cooling and have been widely used in south China. However, few studies focus on the impact of evaporative cooling of different permeable paving materials on the outdoor thermal environment. In this study, two widely used permeable paving materials, sintered ceramic porous brick (CB) and open-graded permeable concrete (PC) were investigated. First, partial immersion tests were performed to characterize the water absorption properties of these materials. The results indicated that CB had a higher water absorption rate and a larger water retaining capacity than PC. Then, field measurements were conducted to evaluate the evaporative cooling performance of these materials. The results indicated that (1) water absorption capacity has an important impact on the evaporative cooling effect of permeable materials, a high upward capillary force could maintain the hydraulic continuity over a long distance, thus effectively prolongs the first stage of evaporation, (2) sprinkling water could reduce the surface temperature of both CB and PC by up to 10 °C and lower the ratio of sensible heat flux to the net shortwave radiation of CB and PC to 13.12% and 29.62%, respectively, (3) compared to non-sprinkling conditions, the maximum air temperature above CB and PC could be decreased by up to 1 °C. Additionally, CB could lower the black globe temperature and wet-bulb globe temperature (WBGT) of 0.5 m by up to 3 °C and 2 °C after sprinkling, respectively, suggesting that sprinkling water can improve thermal comfort above pavements. •Water absorption capacity of permeable pavement affects its evaporative cooling effect.•The evaporative cooling effect of wet ceramic permeable brick could last up to 72 h.•The WBGT above the wet permeable pavements were decreased by up to 2 °C.